Use of the Google Classroom Application in Learning Pandemi Covid-19 at SMAS Muhammadiyah Maumere - Irmawati, Theresia Antonia (EduMatika: Jurnal MIPA, 2022)
This study aims to determine the use of the Google Classroom application and its constraints in learning the Pandemic Covid-19 at SMAS Muhammadiyah Maumere. This research was conducted at SMAS Muhammadiyah Maumere in semester 2 of the 2021/2022 school year. The data source in this study was students and teachers in SMAS Muhammadiyah Maumere. The research method that the researcher uses is a descriptive method with data collection techniques, namely using interviews. Based on the results achieved in this study, it can be seen that, the use of the Google Classroom application in SMAS Muhammadiyah Maumere is the use of the Google Classroom application in learning the Pandemi Covid-19 is already running well, easy to use by teachers and students, the application can also used anywhere and easy to send material and tasks. Constraints faced in the use of the Google Classroom application in learning Pandemi Covid-19 are students who do not understand the material provided, it is difficult to get extensive knowledge, tasks given by teachers are difficult to download and their internet networks are limited. While the obstacle faced by the teacher is that many students do not collect timely assignments and the internet network is limited